A review on data replication strategies in cloud systems. (20th August 2022) - Mokadem, Riad; Martinez-Gil, Jorge; Hameurlain, Abdelkader; Kueng, Josef
Data replication constitutes an important issue in Cloud data management. In this context, a significant number of replication strategies have been proposed for Cloud systems. Most of the studies in the literature have classified these strategies into static vs. dynamic or centralised vs. decentralised strategies. In this paper, we propose a new classification of data replication strategies in Cloud systems. It takes into account several other criteria, specific to Cloud environments: (i) the orientation of the profit, (ii) the considered objective function, (iii) the number of tenant objectives, (iv) the nature of the Cloud environment and (v) the consideration of economic costs. Dealing with the last criterion, we focus on the provider's economic profit and the consideration of energy consumption by the provider. Finally, the impact of some important factors is investigated in a simulation study.